2016
DOI: 10.1158/1940-6207.capr-16-0054
|View full text |Cite
|
Sign up to set email alerts
|

Higher Order Chromatin Modulator Cohesin SA1 Is an Early Biomarker for Colon Carcinogenesis: Race-Specific Implications

Abstract: Alterations in high-order chromatin, with concomitant modulation in gene expression, are one of the earliest events in the development of colorectal cancer (CRC). Cohesins are a family of proteins that modulate high-order chromatin, although the role in CRC remains incompletely understood. We, therefore, assessed the role of cohesin SA1 in CRC biology and as a biomarker focusing in particular on the increased incidence/mortality of CRC among African-Americans (AAs). Immunohistochemistry on tissue arrays reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…nanoarchitecture). Indeed, the convergence of these molecular regulators on physical structure has been observed in studies of multiple chromatin remodelers (Supplemental Figure 1) and correlated with changes in accessibility1415. Therefore, while these descriptions are intuitive for the gene under exploration, they currently do not extend into an integrated model of chromatin physical topology.…”
mentioning
confidence: 99%
“…nanoarchitecture). Indeed, the convergence of these molecular regulators on physical structure has been observed in studies of multiple chromatin remodelers (Supplemental Figure 1) and correlated with changes in accessibility1415. Therefore, while these descriptions are intuitive for the gene under exploration, they currently do not extend into an integrated model of chromatin physical topology.…”
mentioning
confidence: 99%
“…Furthermore, the racial predilection may explain, at least partly, the striking differences in CRC rates for Blacks compared to Whites. The patient database was small and thus the odds ratio for CRC was not significant but the decreased colonic SA-1 expression is compelling given the unequivocal data that SA-1 down-regulation is an earliest event in colon carcinogenesis [27] .…”
Section: Discussionmentioning
confidence: 99%
“…The cohesins, including SA-1 (also known as STAG1 and SCC3 ), are a recently discovered high order chromatin remodellors that are involved in chromatin looping (bringing enhancers/promoters in proximity to coding regions to foster transcription) and thus facilitate long-range nuclear interactions and gene expression [13] . While mutations in this family of proteins are rare in CRC, we have recently reported that SA-1 was significantly down-regulated in the endoscopically normal rectal mucosa of patients harboring adenomas elsewhere in their colon (field carcinogenesis) presumably through epigenetic mechanisms [14] . Moreover, SA-1 loss triggered critical pathways in carcinogenesis [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 98%
“…In this view, changes in DNA methylation (CpG islands), histone modifications, and mutations in both higher-order chromatin modulators (cohesins, condensins) and histone modifying enzymes (HDACs, SWItch/Sucrose nonfermentable enzymes) could be convergent on global changes that act at the level of a genomic ‘folding code’ [ 49–53 ]. Interestingly, PWS microscopy has shown that some of these alterations are manifested in transformation of the physical structure of chromatin [ 25 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%